Lexicography of the Portuguese language and Dialectology: weaving networks of knowledge - Paim, Marcela Moura Torres (2019)
In this paper, we aim to discuss the relation between Lexicography and Dialectology in the use of school dictionaries for Brazilian Portuguese language learners. We analyze linguistic data collected from both the Brazilian Linguistic Atlas Project (ALiB) and school dictionary entries so as to verify whether the gathered data in ALIB Project were considered in those lexicographic works. Based on the observation of these dictionaries, we deduce that the analyzed ones do not include enough dialectal information and they miss oral language data, which reveals that there is a lack of integration with data collected in geolinguistic surveys.